Analysis on distance learning during the Covid-19 emergency, edited by S. Capogna, F. Musella and L. Cianfriglia, Eurilink University Press, Rome, 2021 - Cecchini, Giulia (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The book entitled "Analysis of distance learning during the Covid-19 emergency" offers an interesting reflection on the effects of the pandemic on learning and skills development processes in educational institutions, highlighting in general the intensification of certain phenomena including, the ability to devise strategies and actions pertinent to changes in the external environment; or again, the difficulty in reorganising policy, management and orientation actions of educational activities to which all those figures who, in various capacities, contribute to respond to the growing challenges faced by schools are called upon.